Análise técnica e econômica do processo de obtenção de espaguetes com adição de farinha de trigo integral e farinha de linhaça - Bakker, Christiane Maria Christina Nobrega (2010)
This work studies the fabrication of spaghetti through the process at high temperatures through the use of flour added to flour and flaxseed meal, with the aim of evaluating the final product quality and estimate the cost of production. The values of moisture, ash, protein, wet gluten, gluten index, falling number and grain of flour and mixtures to test to be the possible use in mass manufacturing and technological criteria for compliance with current legislation. Spaghetti noodles type were manufactured by adding 10% and 20% flour and 10% and 20% flaxseed meal with performance of physical-chemical, sensory and rheological properties of the products. Further analysis was performed on the product acceptance and estimation of production cost in order to create subsidies to enable the introduction of products with greater acceptance and economic viability in the market by the food industry. On the rheology of the product test was cooking the pasta, specifying the volume increase, cooking time and percentage of solid waste. In the sensory evaluation was carried out the triangular test of product differentiation with 50 trained judges and acceptance testing by a hedonic scale with evaluation of the aspects color, taste, smell and texture. In defining the sensory profile of the product was performed with ADQ 9 judges recruited and trained at the factory, using unstructured scale of 9 cm, assessing the attributes of flavor of wheat, flax flavor, consistency, texture of raw pasta, raw pasta color and color of cooked pasta. The greater acceptance of product quality was good and the pasta with 20% flour, 10% followed by the full product, 10% and 20% flaxseed characterized the average quality of the criterion of loss analysis of solids, together with mass full commercial testing. In assessing the estimated cost of production, the two products more technologically feasible and acceptable (20% whole and 10% flaxseed) were evaluated in high temperature processes. With total cost of R $ 4,872.5 / 1,000 kg and R $ 5,354.9 / 1,000 kg respectively, the difference was related to the addition of lower inputs and higher added value in the market, flour and flaxseed meal. The comparative analysis of cases was confirmed the reduction in production time (10h), more uniform product to the drying process at high temperature compared to conventional